Repeated Batch Process for Glucoamylase Production by Aspergillus niger - Vasanthy, A. (University of Jaffna, 2019)
Production of glucoamylase (amyloglucosidase) by Aspergillus niger was studied in batch and repeated batch submerged fermentations. In batch culture, growth (biomass 35.8 gL-1) and glucoamylase production (53.2 UmL-1) were highest at 108 h (4.5 days). Addition of spores on the 4th and 8th days to augment the old mycelium extended the glucoamylase production up to 9 days. When the spent medium was supplemented with soluble starch from manioc (50 gL-1) on the 4.5th day, glucoamylase activity increased by 14.6 UmL-1 on the 6th day [one and a half day (36 h) after the addition of starch]. Replacement of the spent medium with the fresh fermentation medium on the 4th day, led to 70.3 UmL-1 glucoamylase activities on the 7th day (3rd day after the addition of the fresh fermentation medium). The spent medium was replaced with the fresh fermentation medium along with the addition of spores led to an increase in the glucoamylase production by 1.62 and 1.66 folds in the 2nd and the 3rd cycles of that obtained in the first cycle. Thus fed batch process was not possible under the conditions considered for glucoamylase production while repeated batch process seems to be promising.
Keywords: Aspergillus niger; Biomass; Glucoamylase; NADPH; Repeated batch process